Pengaruh Self Service Technology (SST) terhadap Customer Loyalty yang Dimediasi oleh Customer Satisfaction - Maulidia, Annisa; Zuhra, Syarifah Evi (Syiah Kuala University Press, 2024)
This research aims to measure the influence of Self Service Technology (SST) on Customer Loyalty mediated by Customer Satisfaction in Kopi Kenangan customers in Banda Aceh City. The sample used in this research was Kopi Kenangan customers who had made purchases through the Kopi Kenangan application at least twice and were located in Banda Aceh City. The respondents in this research were 160 respondents. The sampling technique used was Purposive Sampling. Data analysis uses the Structural Equation Modeling (SEM) model with the analysis method using Confirmator Factor Analysis (CFA) using the AMOS program tools.The research results show that Self Service Technology (SST), Customer Satisfaction and Customer Loyalty at the Kopi Kenangan outlet in Banda Aceh City are good. Self Service Technology (SST) influences Customer Loyalty, Self Service Technology (SST) influences Customer Satisfaction, Customer Satisfaction influences Customer Loyalty, and Customer Satisfaction partially mediate the influences of Self Service Technology (SST) on Customer Loyalty.